2021
DOI: 10.1016/j.vhri.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Challenges in Health Technology Assessment Institutionalization for Furtherance of Universal Health Coverage Through South-South Knowledge Exchange: Lessons From Bhutan, Kenya, Thailand, and Zambia

Abstract: Health Technology Assessment (HTA), a tool for priority setting, has emerged as a means of ensuring the sustainability of a Universal Health Coverage (UHC) system. However, setting up an effective HTA system poses multiple challenges and knowledge exchange can play a crucial role in helping countries achieve their UHC targets. This article reports the results of the discussion during a preconference session at the 2019 HTAsiaLink Conference, an annual gathering of HTA agencies in Asia, which supports knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…With a decline in donor funding due to the global recession ( 58 , 59 ), governments should earmark funds for research in priority setting in health, including preventive programs such as screening to guide investments and ensure the sustainability of universal health coverage programs. There is also a need for strategic investments to build the capacity of both users (policymakers and high-level managers) and suppliers (academics, research organizations) of health technology assessments to ensure the agenda for priority setting is locally driven ( 45 , 46 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a decline in donor funding due to the global recession ( 58 , 59 ), governments should earmark funds for research in priority setting in health, including preventive programs such as screening to guide investments and ensure the sustainability of universal health coverage programs. There is also a need for strategic investments to build the capacity of both users (policymakers and high-level managers) and suppliers (academics, research organizations) of health technology assessments to ensure the agenda for priority setting is locally driven ( 45 , 46 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…On-the-job training has been catalytical for many countries in building HTA capacity in Southeast Asia. Networks form an important element of connecting researchers with one-another and institutional arrangements to attract and retain staff trained in HTA is another area that needs to be considered [ 24 ]. Online resources such as the Guide to Health Economic Analysis and Research (GEAR) also offer researchers in LMICs to connect with global experts in the field [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to this framework, Knowledge creation, or the production of knowledge, is composed of; knowledge inquiry, synthesis of knowledge and creation of knowledge tools. As knowledge is distilled through each stage in the knowledge creation process, the resulting knowledge becomes more synthesized and potentially more useful to end-users (24).…”
Section: Knowledge Translation Matters!mentioning
confidence: 99%
“…The interactive-recursive model of knowledge transfer can serve as a basis for the identification and analysis of potential transfer barriers. Based on the assumptions that first; research projects lead to positive results respectively solutions are found for previously defined problems, and secondly; the existence of these solutions is known to a circle of potential knowledge-takers, barriers of knowledge transfer (24). Study done by Dagenais, C. (2021) in Burkina Faso to determine research use at the Ministry of Health (MoH) revealed that apart from the sometimes unwillingness to support research, the main obstacles identified were; the difficulties of accessing research results, the insufficiency in dissemination and lack of action plans to apply those results were rarely proposed in the findings (22); Given that "we can't use what we don't know exists," the issue of access to research results is fundamental, and such access must be timely.…”
Section: Obstacles To Knowledge Translationmentioning
confidence: 99%